Modification of classification of methods of local anesthesia (LLC "Endo Press", 2020)
Given the proven in a series of recent scientific papers leading vascular component of the mechanism of spongy injections, traditional classification techniques of dental local anesthesia needs to be transformed. We offer its modification, which is to split all ways on diffuse and vascular diffuse. Diffuse anesthesia includes application, infiltration and conduction. Vascular diffuse include intraosseous, intraligamentary, intraseptal and intrapulpal. For the last 4 methods, you can use the term spongy (intraosseous) anesthesia.